Serum Analysis of Adeno-associated Virus 2 and Some Cell-cycle Regulatory Protein Levels in a Group of Iraqi Patients with Hepatocellular Carcinoma - Jasim Mohammed Muhsin; Zainab Jumaah Fadhil; Mustafa Ahmed Dawood (Biomedical and Biotechnology Research Journal)
Background: Hepatocellular carcinoma (HCC) can arise in a wide variety of situations and have different etiologies. Recently discovered as novel HCC cofactors are adeno-associated virus 2 (AAV2) insertional mutagenesis and phosphatase–tensin homolog (PTEN) overexpression. The objective of this study was to determine the prevalence of AAV2 antibodies in Iraqi HCC patients as well as how AAV2 antibody titers affect the levels of some group of cell-cycle regulatory proteins in the blood as a serological study. Methods: For this study, a total of 61 Iraqi volunteers were enrolled, 30 of whom had HCC and underwent surgery in 2024 at a gastroenterology and hepatology teaching hospital in Baghdad (including 16 hepatitis B-related cases, 10 hepatitis C-related cases, 4 different-related cases, besides 31 viral seronegative as controls). Serum samples were examined using an enzyme-linked immunosorbent assay to determine the concentrations of AAV2, cyclin A2, cyclin E1, telomerase reverse transcriptase, and PTEN. Results: The detection rate of AAV2 antibodies was fairly high, 43 (70.5%) in the people with AAV2-related HCC, and no clinical signs of liver cirrhosis were seen. In addition, there was a strong correlation between the high level of serum PTEN concentration and AAV2 seropositivity (P = 0.0001). Conclusion: Our serological results support the previous molecular idea that PTEN overexpression and AAV2 play critical roles in the development of HCC.